The calls of Islam: Sufis, Islamists, and mass mediation in urban Morocco - Spadola, Emilio (Public cultures of the Middle East and North Africa, 2014)
Cover; Contents; Acknowledgments; Note on Transliteration; Introduction; 1 Competing Calls in Urban Morocco; 2 Nationalizing the Call: Trance, Technology, and Control; 3 Our Master's Call: The Apotheosis of Moroccan Islam; 4 Summoning in Secret: Mute Letters and Veiled Writing; 5 Rites of Reception; 6 Trance-Nationalism, or, the Call of Moroccan Islam; 7 "To Eliminate the Ghostly Element Between People": The Call as Exorcism; Epilogue; Notes; References; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Z.